Local Historical Learning In Multicultural Education In The Era Of Merdeka Learning - Ivan Prapanca Wardhana; Leo Agung S; Susanto Susanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
History is a science that has a very big mission to improve human civilization, history provides many lessons about important concepts in facing the life to come. Multicultural education is a process of developing all human potential that respects plurality and heterogeneity as a consequence of cultural, ethnic, ethnic and religious (religious), economic, social, and political diversity. This study uses a literature study research method by collecting data from both document books, international and national journals, theses, proceeding articles, and websites related to the object of research then analyzed by text analysis techniques. As stated in the basic competencies in history lessons, it is implied to grow and instill multicultural education and national identity. Basically, national identity makes the hallmark of a nation which aims to instill character values and respect for the people in the culture and ethnic races that exist in Indonesia during the Free Learning era which is currently being implemented in the education system in Indonesia.